2010
DOI: 10.1038/nature09114
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study in alopecia areata implicates both innate and adaptive immunity

Abstract: Alopecia areata (AA) is among the most highly prevalent human autoimmune diseases, leading to disfiguring hair loss due to the collapse of immune privilege of the hair follicle and subsequent autoimmune attack1,2. The genetic basis of AA is largely unknown. We undertook a genome-wide association study (GWAS) in a sample of 1,054 cases and 3,278 controls and identified 139 single nucleotide polymorphisms that are significantly associated with AA (P ≤ 5 × 10 −7 ). Here we show © 2010 Macmillan Publishers Limited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
647
3
17

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 678 publications
(703 citation statements)
references
References 38 publications
18
647
3
17
Order By: Relevance
“…Indeed, focal T lymphocytes infiltration [4] and deposition of hair folliclespecific autoantibodies [5] are present in anagen stage (growing) hair follicles. Susceptibility to AA has been referred to a polygenic complex [6,7] comprising immune system genes coding for the human leukocyte antigens (HLA) or other immune-related gene products [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, focal T lymphocytes infiltration [4] and deposition of hair folliclespecific autoantibodies [5] are present in anagen stage (growing) hair follicles. Susceptibility to AA has been referred to a polygenic complex [6,7] comprising immune system genes coding for the human leukocyte antigens (HLA) or other immune-related gene products [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This weak association is in line with the findings of a GWAS conducted in a Caucasian population. 126 The association between PTPN22 C1858T and primary Sjogren's syndrome (pSS) is not clear. One study from Columbia (70 cases and 308 controls) identified a strong association (OR ¼ 2.42; 95% CI ¼ 1.23-4.75, P ¼ 0.01); this was similar to that for SLE, but stronger than that for RA or T1D in the same population.…”
Section: Diseases Showing No or Weak Association With Ptpn22mentioning
confidence: 99%
“…These polymorphisms (IL2/IL21, IL2RA, CTLA4, IK2F4, HLA, NK-activating ligands, ILBP6, ULBP6, STX17, PRDX5) were found be associated with T cells or the hair follicle. In addition, there was a region of strong association on the cytomegalovirus UL16-Binding Protein Gene Cluster (ULBP) [9]. This gene cluster encodes the activating ligands of natural killer cell receptor NKG2D.…”
Section: Geneticsmentioning
confidence: 99%
“…139 single nucleotide polymorphisms have been identified in 8 regions of the genome [9]. These polymorphisms (IL2/IL21, IL2RA, CTLA4, IK2F4, HLA, NK-activating ligands, ILBP6, ULBP6, STX17, PRDX5) were found be associated with T cells or the hair follicle.…”
Section: Geneticsmentioning
confidence: 99%